Green bottle packaging design for micro, small, and medium enterprises (SME) - Musdalifah, Musdalifah; Asmal, Sapta; Parenreng, Syarifuddin M. (Journal Industrial Servicess, 2023)
Plastic bottle waste constitutes a significant part of plastic waste. The extensive use of plastic bottles for packaging generates a substantial volume of waste, particularly those made from polyethylene terephthalate polymers, with high carbon chain content, resulting in slow decomposition. UMKM Markisa is among the businesses employing plastic bottles for packaging. This study aims to develop a green manufacturing strategy for MSMEs, focusing on consumer distribution. Employing the Kano and HOQ methods, the study seeks to identify consumer-desired attributes for Passion Fruit Aurora products and prioritize product development. Through 15 questionnaires distributed to 100 consumers, the study identified three attributes with the highest ratings: 16% for the choice of packaging materials, 13% for recyclable packaging, and 9% for redesigning the packaging. The research concludes by recommending the adoption of eco-friendly plastic packaging using PLA material, ensuring easier decomposition and environmental safety due to its plant-based origin. This proposal also suggests incorporating an attractive design, emphasizing the need for all MSMEs to embrace environmentally sustainable packaging.